Development of pyrazole and spiropyrazoline analogs as multifunctional agents for treatment of Alzheimer's disease - Gutti G.; Kumar D.; Paliwal P.; Ganeshpurkar A.; Lahre K.; Kumar A.; Krishnamurthy S.; Singh S.K. (My University, 2025)
Cholinergic hypothesis of Alzheimer's disease has been advocated as an essential tool in the last couple of decades for the drug development. Here in, we report de novo fragment growing strategy for the design of novel 3,5-diarylpyrazoles and hit optimization of spiropyrazoline derivatives as acetyl cholinesterase inhibitors. Both type of scaffolds numbering forty compounds were synthesized and evaluated for their potencies against AChE, BuChE and PAMPA. Introduction of lipophilic cyclohexane ring in 3,5-diarylpyrazole analogs led to spiropyrazoline derivatives, which facilitated and improved the potencies. Compound 44 (AChE = 1.937 ± 0.066 µM; BuChE = 1.166 ± 0.088 µM; hAChE = 1.758 ± 0.095 µM; Pe = 9.491 ± 0.34 × 10−6 cm s1) showed positive results, which on further optimization led to the development of compound 67 (AChE = 0.464 ± 0.166 µM; BuChE = 0.754 ± 0.121 µM; hAChE = 0.472 ± 0.042 µM; Pe = 13.92 ± 0.022 × 10−6 cm s1). Compounds 44 and 67 produced significant displacement of propidium iodide from the peripheral anionic site (PAS) of AChE. They were found to be safer to MC65 cells and decreased metal induced Aβ1-42 aggregation. Further, in-vivo behavioral studies, on scopolamine induced amnesia model, the compounds resulted in better percentage spontaneous alternation scores and were safe, had no influence on locomotion in tested animal groups at dose of 3 mg/kg. Early pharmacokinetic assessment of optimized hit molecules was supportive for further drug development. © 2019 Elsevier Inc.